دراسة مقارنة لأثر الالوان على دقة التهديف لدى لاعبى كرة الصالات منتخب جامعة كوية - جلال, ناظم جبار; حسين, اوات علي (Sulaimani Journal for Humanities, 2018)
The research aims to: - Identify the impact of colors on the accuracy of the players scoring football team pentathlon Koya University. The researcher used the descriptive style relational relations. The research sample identified players on the team Koya University football Penta's (10) for a player out (12) player. At a rate (83.3%) have been selected in a deliberate manner. Also identified the equipment and tools used in the search. As well as the identification of test scoring Futsal. The tests were also conducted reconnaissance for the purpose of experience to know the validity of the measures in the field. The statistical methods were used for the purpose of data processing that serves the search. The researcher reached conclusions of the most important: * Lack of significant differences in accuracy between colors correction, but there is a difference in the homogeneity of the sample in performance over the testing of different colors. * There is a positive effect of color correction to increase the accuracy of Precision be more in the case of color correction on targets and moral this Makdth differences on the accuracy of color correction on the areas and non-colored areas. * Achieved red largest center of my account while has less white middle of my account. * The best center-Wish accuracy correction was on the red box. The researcher recommends the following: * Colors should be used in educational and training aids for the development and the development of accurate correction, especially bright colors and bright, particularly red. As colors may not be used haphazardly. * conduct research to know the effect of all colors after distribution in the form of color groups, taking into account the personality traits relevant for athletes in color. Attention to the quality of the colors of clothing worn by players